Предмет: Математика,
автор: АннаЕрмак
-1.4(х-6)=7(4х+1.2)
Помогите
Ответы
Автор ответа:
0
-1.4(х-6)=7(4х+1.2)
-1,4х+8,4=28х+8,4
28х+1,4х=8,4-8,4
29,4х=0
х=0
-1,4х+8,4=28х+8,4
28х+1,4х=8,4-8,4
29,4х=0
х=0
Автор ответа:
0
-1.4(х-6)=7(4х+1.2)
-1.4х-6*(-1.4)=7*4х+1.2*7
-1.4х-(-8,4)=28х+8,4
-1,4х+8,4=28х+8,4
-1,4х-28х=8,4-8,4
-29,4х=0
х=0
-1.4х-6*(-1.4)=7*4х+1.2*7
-1.4х-(-8,4)=28х+8,4
-1,4х+8,4=28х+8,4
-1,4х-28х=8,4-8,4
-29,4х=0
х=0
Похожие вопросы
Предмет: Математика,
автор: sofiacat0508
Предмет: Физика,
автор: kseniiia05632
Предмет: История,
автор: privetikznanija0
Предмет: Литература,
автор: polli511
Предмет: История,
автор: gasoyannaira